Revolusi Digital Maritim: Analisis Yuridis Keamanan Siber di Pelabuhan dan Kekuatan Pembuktian Electronic Bill of Lading - Alfian Alfian; Mariani Loise; Andi Suryani (Journal of Innovative and Creativity, 2025)
This study analyzes the juridical implications of the maritime digital revolution in Indonesia, focusing on two critical pillars: port cybersecurity and the evidentiary strength of the Electronic Bill of Lading (E-B/L). The purpose is to identify the legal gaps created by the rapid adoption of digital technology, which has outpaced the existing legal framework, resulting in a significant 'regulatory lag' and 'digital trust deficit.' This research applies a normative juridical approach, supported by a statute approach to analyze regulatory conflicts and a comparative approach to benchmark against international instruments like the UNCITRAL Model Law on Electronic Transferable Records (MLETR) and IMO guidelines. Primary legal materials, including the Indonesian Commercial Code (KUHD) and the Law on Electronic Information and Transactions (ITE Law), are analyzed alongside secondary materials from academic journals and policy papers. The findings reveal two major gaps: (1) cybersecurity regulations for ports as Vital Information Infrastructure (IIV) are largely voluntary, lacking a mandatory, enforceable liability framework; and (2) the E-B/L faces significant legal uncertainty, as its function as a 'document of title' conflicts with the paper-based assumptions of the KUHD, despite de jure recognition from the ITE Law. The study concludes that Indonesia requires urgent legal harmonization. Strengthening the digital maritime ecosystem necessitates establishing a mandatory cybersecurity framework for ports and ratifying international instruments to provide full legal certainty for the E-B/L, thereby bridging the gap between technological advancement and legal preparedness.